Perbedaan Disfungsi Sexual Wanita yang Melahirkan Secara Pervaginam dengan Episiotomy Mediolateral dan Seksio Sesarea - Irwanto, Yahya; Mustofa, Edy (Journal of Issues in Midwifery, 2018)
Generally, the causes of Postpartum Female Sexual Dysfunction (PPFSD) are dyspareunia, perineal pain, the discomfort of incision lesion including surgery, reduction of libido, lack of lubrication in the vagina, changes in seeing body image to be negative, and anorgasm irelated to pain and trauma. Perineal pain and dyspareunia are post partum problems which occur frequently and interfere with normal sexual function, that usually are caused by perineal trauma, episiotomy, and child birth instrumentation.This study was conducted by a cross-sectional study. Research subjects consisted of women  post vaginal delivery with mediolateral episiotomy and postcesarean section. Each group consisted of 45  people. After three months post partum sexual function as sessed using FSFI scores (Female Sexual Function Index) as well as an assess ment of demographic data include age, religion, education, employment, insurance coverage/BPJS, gestational age, birthweight, stitches condition, medical treatment, nursing, assistance of baby sitter and problems in the family. The data had to fulfill the inclusion and exclusion criteria in the form of question naires were further tested withc hi-square analysis and independent t-test.In the demographic data analysis withc hi-squareanalys is didn’t find any significant differences  between the two groups, with p>0.05. The sexual dysfunction among women after vaginal delivery  with mediolateral episiotomy and cesarean section  there was no significant difference p=0.081, and p>0.05. On the FSFI scores domains there are significant differences between the two group son the variables of sexual  desire, orgasm, pain and FSFI total scores.